A Link Between Plasma Microbial Translocation, Microbiome, and Autoantibody Development in First‐Degree Relatives of Systemic Lupus Erythematosus Patients. Issue 11 (27th September 2019) - Ogunrinde, Elizabeth; Zhou, Zejun; Luo, Zhenwu; Alekseyenko, Alexander; Li, Quan‐Zhen; Macedo, Danielle; Kamen, Diane L.; Oates, Jim C.; Gilkeson, Gary S.; Jiang, Wei
Abstract : Objective: Systemic lupus erythematosus (SLE) is characterized by the production of antibodies against self antigens. However, the events underlying autoantibody formation in SLE remain unclear. This study was undertaken to investigate the role of plasma autoantibody levels, microbial translocation, and the microbiome in SLE. Methods: Plasma samples from 2 cohorts, one with 18 unrelated healthy controls and 18 first‐degree relatives and the other with 19 healthy controls and 21 SLE patients, were assessed for autoantibody levels by autoantigen microarray analysis, measurement of lipopolysaccharide (LPS) levels by Limulus amebocyte assay, and determination of microbiome composition by microbial 16S ribosomal DNA sequencing. Results: First‐degree relatives and SLE patients exhibited increased plasma autoantibody levels compared to their control groups. Parents and children of lupus patients exhibited elevated plasma LPS levels compared to controls ( P = 0.02). Plasma LPS levels positively correlated with plasma anti–double‐stranded DNA IgG levels in first‐degree relatives (r = 0.51, P = 0.03), but not in SLE patients. Circulating microbiome analysis revealed that first‐degree relatives had significantly reduced microbiome diversity compared to their controls (observed species, P = 0.004; Chao1 index, P = 0.005), but this reduction was not observed in SLE patients. The majority of bacteria that were differentially abundant between unrelated healthy controls and first‐degree relatives were in the Firmicutes phylum, while differences in bacteria from several phyla were identified between healthy controls and SLE patients. Bacteria in the Paenibacillus genus were the only overlapping differentially abundant bacteria in both cohorts, and were reduced in first‐degree relatives (adjusted P [ P adj ] = 2.13 × 10 −12 ) and SLE patients ( P adj = 0.008) but elevated in controls. Conclusions: These results indicate a possible role of plasma microbial translocation and microbiome composition in influencing autoantibody development in SLE.